METHODS OF RESPONSIBILITY FORMATION IN CHILDREN IN PREPARATION FOR SCHOOL - Karimova Umida Sharipovna (American Journals, 2025)
The article provides information on the possibilities of using personal-activity and axiological approaches in the design of educational and cognitive activities of primary school students.
Keywords: responsibility, preschool education, preparation for school.